Establishing a Urine-Based Biomarker Assay for Prostate Cancer Risk Stratification - Guo, Jinan; Liu, Dale; Zhang, Xuhui; Johnson, Heather; Feng, Xiaoyan; Zhang, Heqiu; Wu, Alan H. B.; Chen, Lingwu; Fang, Jiequn; Xiao, Zhangang; Xiao, Kefeng; Persson, Jenny L.; et al. (Frontiers in Cell and Developmental Biology, 2020)
One of the major features of prostate cancer (PCa) is its heterogeneity, which often leads to uncertainty in cancer diagnostics and un-necessary biopsies as well as overtreatment of the disease. Novel non-invasive tests using multiple biomarkers that can identify clinically high risk cancer patients for immediate treatment and monitor patients with low risk cancer for active surveillance are urgently needed to improve treatment decision and cancer management. In this study, we identified fourteen promising biomarkers associated with PCa and tested the performance of these biomarkers on tissue specimens and pre-biopsy urinary sediments. These biomarkers showed differential gene expression in higher and lower risk PCa. The 14-Gene Panel urine test (PMP22, GOLM1, LMTK2, EZH2, GSTP1, PCA3, VEGFA, CST3, PTEN, PIP5K1A, CDK1, TMPRSS2, ANXA3, and CCND1) was assessed in two independent prospective and retrospective urine study cohorts and showed high diagnostic accuracy to identify higher risk PCa patients with the need for treatment and lower risk patients for surveillance. The AUC was 0.897 (95% CI 0.939-0.855) in the prospective cohort (n=202) and 0.899 (95% CI 0.964-0.834) in the retrospective cohort (n=97). In contrast, serum PSA and Gleason score had much lower accuracy in the prospective cohort (AUC was 0.821 (95% CI 0.879-0.763) for PSA and 0.860 (95% CI 0.910-0.810) for Gleason score). In addition, the 14-Gene Panel was more accurate at risk stratification in a subgroup of patients with Gleason score 6 and 7 in the prospective cohort (n=132) with AUC of 0.923 (95% CI 0.968-0.878) than PSA (AUC of 0.773 (95% CI 0.852-0.794)) and Gleason score (AUC of 0.776 (95% CI 0.854-0.698)). Furthermore, the 14-Gene Panel was found to be able to accurately distinguish PCa from benign prostate with AUC of 0.854 (95% CI 0.892-0.816) in a prospective urine study cohort (n=393), while PSA had lower accuracy with AUC of 0.652 (95% CI 0.706-0.598). Taken together, the 14-Gene Panel urine test represents a promising non-invasive tool for detection of higher risk PCa to aid treatment decision and lower risk PCa for active surveillance.